Ohio Proficiency Tests for Grade 12. Practice Test - Ohio State Dept. of Education, Columbus; Ohio State Dept. of Education, Columbus ([S.l.] : Distributed by ERIC Clearinghouse, 1995)
High school seniors in Ohio who have passed all parts of the ninth-grade proficiency tests are required to take the twelfth-grade proficiency tests. These tests, in writing, reading, mathematics, citizenship, and science, are designed to measure twelfth-grade performance and to evaluate the learning that goes on between the minimum competencies of the ninth grade and the first semester of the senior year. This practice test is designed to be used by students individually or in groups. Included in this booklet are a detachable answer sheet, the practice test, directions for scoring the writing section, sample student papers, an answer key, and an outline of specific learning outcomes illustrated in each test area. The practice test is not designed to predict student performance on the actual tests, but is meant only to provide examples of the kinds of questions students will encounter. (SLD)
ERIC Note: For related documents, see TM 025 963 and 025 965.
Students.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Achievement Tests; Citizenship Education; Graduation Requirements; High School Seniors; High Schools; Mathematics Tests; Outcomes of Education; Reading Tests; Science Tests; Scoring; Writing Tests; Practice Tests; Ohio Twelfth Grade Proficiency Test; Tests/Questionnaires.